Corporate social responsibility and its impact on consumer behaviour - a consumer's perspective. (2016) - Barkakati, Unmana; Patra, Raj Kishore; Das, Payel
Of late, corporate social responsibility (CSR) has become the edict for most businesses. However, there is no thorough measurement available on the impact of CSR initiatives on business performance yet, CSR is believed to have a positive relationship with a company's goodwill and thereby have a positive impact on consumer's behaviour. This empirical exploration embarks on investigating the influence of CSR practices on a company's image and reputation with special reference to fast moving consumer goods (FMCG) companies and, in turn, on public opinion relating to the business. Further, the study empirically examines the influence of CSR practices on a consumer's buying decision process and also validates if customers react to CSR activities in a similar way or does it vary as per different demographics.